FINANCIAL PERFORMANCE IN PREDICTING THE VALUE OF SYARIAH STOCK OF FOOD AND BEVERAGES COMPANIES: THE ROLE OF DIVIDEND POLICY AS MODERATION [KINERJA KEUANGAN DALAM MEMPREDIKSI NILAI SAHAM SYARIAH PERUSAHAAN MAKANAN DAN MINUMAN: PERAN KEBIJAKAN DIVIDEN SEBAGAI MODERASI] - Aisah, Nurul; Rofifudin, Farid Muhammad; Rahmawati, Nur (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze financial performance in predicting stock value and offers a new perspective by exploring how dividend policy can strengthen or weaken the influence of financial performance on the stock value of Sharia Food and Beverages Stock companies. This type of research uses a quantitative approach. Data analysis used in this study is using panel data regression with a purposive sampling method. The population in this study were 7 food and beverage sector companies in the sharia stock category in 2018-2023. While the sample in this study was the annual financial reports of 7 food and beverage sector companies in the sharia stock category in 2018-2023 as many as 42 data. And the results of the hypothesis test show that the ROA, Current Ratio, DER and TATO variables have a significant positive effect on Stock Price, in addition, dividend policy is able to moderate the effect of the Current Ratio, DER and TATO variables on Stock Price. However, dividend policy does not moderate the effect of the ROA variable on Stock Price. This finding implies that the company's financial performance in general has an important role in determining investor perceptions of the company's stock value. Thus, company management needs to pay attention to increasing the efficiency of asset use (TATO), liquidity (Current Ratio), and capital structure (DER), as well as the ability to generate profits (ROA) to attract investor interest and encourage an increase in share prices